2021
DOI: 10.1088/1361-6552/ac3dc5
|View full text |Cite
|
Sign up to set email alerts
|

Online versus face-to-face learning in introductory university physics following COVID-19

Abstract: The use of technology in higher education science classrooms rose significantly in the advent of the COVID-19 pandemic. In many universities, academic programs including introductory physics classes were taken online. Some institutions adopted online learning but also maintained face-to-face (F2F) laboratories when COVID-19 restrictions began to ease. Here, the effectiveness of the online learning approach in comparison with F2F learning is explored. The percentage difference in performance for students who to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…These findings are consistent with those of research showing that students may respond differently to face-to-face and online mediums, and some may even perform better online (Cole et al, 2017;Fendler et al, 2018;Kurucay & Inan, 2017). In the selected physics course, our findings are consistent with those of Fouad et al (2021) who reported higher performance online, but inconsistent with those of Faulconer et al (2018) who reported no significant differences between synchronous online and face-to-face physics for withdrawal rates, failure rates, and grades.…”
Section: The Findingscontrasting
confidence: 86%
See 1 more Smart Citation
“…These findings are consistent with those of research showing that students may respond differently to face-to-face and online mediums, and some may even perform better online (Cole et al, 2017;Fendler et al, 2018;Kurucay & Inan, 2017). In the selected physics course, our findings are consistent with those of Fouad et al (2021) who reported higher performance online, but inconsistent with those of Faulconer et al (2018) who reported no significant differences between synchronous online and face-to-face physics for withdrawal rates, failure rates, and grades.…”
Section: The Findingscontrasting
confidence: 86%
“…Unsurprisingly, the results are mixed. For instance, Fouad et al (2021) who examined students' performance in this course as a function of synchronous (real‐time) online and face‐to‐face mediums, reported higher performance online. Instead, Faulconer et al (2018) reported no significant differences between synchronous online and face‐to‐face physics for withdrawal rates, failure rates, and grades.…”
Section: Introductionmentioning
confidence: 99%
“…In the end, Education decisively turned to the direction resisted for years: massive Internet use [46]. Even today, during the "New Normal," not all actors worldwide have embraced the experience, continuing to resist using the Internet for online or blended education, instead of capitalizing on the experience and achieving educational goals [47,48].…”
Section: Research Digital Transformation Accelerated By the Covid-19 ...mentioning
confidence: 99%
“…Although there was a great deal of skepticism from the State University faculty as to online university coursework in general, the literature often discusses and favorably compares online courses to in-person formats (Kenzig, 2015). For example, Fouad et al (2021) found that students in online sections scored slightly better than their peers in in-person sections. Soffer and Nachmias (2018) found that students taking the profiled online courses reported higher grades, as well as higher engagement and satisfaction, compared to the profiled in-person course with the same instructor and final exam (Soffer & Nachmias, 2018).…”
Section: Strong Bias Against Online Learningmentioning
confidence: 99%
“…They typically highlight their positive regard for the central presence of the teacher and their difficulties with self-regulated learning online (Guskaroska et al, 2022). Fouad et al (2021) found that 72% of students prefer in-person courses. In addition to favoring in-person courses, students tend to favor synchronous online courses as opposed to asynchronous alternatives, and students who do favor the asynchronous modality seem to prefer it due to its flexibility rather than a pure "learning style" preference (Bonnici et al, 2016).…”
Section: Challenges With Online Courses and Ertmentioning
confidence: 99%